2019
DOI: 10.1186/s13018-019-1311-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between cortical screws and traditional pedicle screws for lumbar interbody fusion: a systematic review and meta-analysis

Abstract: Purpose The clinical outcomes of using a cortical screw (CS) for lumbar interbody fusion were evaluated by comparison with conventional pedicle screw (PS) fixation. Methods All of the comparative studies published in the PubMed, Cochrane Library, MEDLINE, Web of Science, and EMBASE databases recently as 18 March 2019, were included. All outcomes were analyzed by using Review Manager 5.3. Results Twelve studies were included with a total of 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
2
15
1
Order By: Relevance
“…Significant changes were identified between the two groups in average surgical time, intraoperative blood loss and length of incision. The results were consistent with that in similar cohorts [31]. The average surgical time ranged from 117.8min to 237.6min [8,20], and 119ml to 276.5ml [21,32] for intraoperative blood loss in previous studies of single level cortical screw fixation surgery [21,[32][33][34].…”
Section: More Familiar With Surgical Procedures: a Natural Processsupporting
confidence: 87%
“…Significant changes were identified between the two groups in average surgical time, intraoperative blood loss and length of incision. The results were consistent with that in similar cohorts [31]. The average surgical time ranged from 117.8min to 237.6min [8,20], and 119ml to 276.5ml [21,32] for intraoperative blood loss in previous studies of single level cortical screw fixation surgery [21,[32][33][34].…”
Section: More Familiar With Surgical Procedures: a Natural Processsupporting
confidence: 87%
“…But according to the author of this study, there was no difference between the two methods except on low back pain improvement, increased or comparable blood loss in the CBT group than pedicle screw (PS) group. Previous studies have reported benefits of less blood loss, less hospital stay, and less incision length in CBT patients when compared to the traditional pedicle trajectory screws technique [2][3][4]. This is in conflict and contrast to this study with no explanations put forth for this significant finding.…”
contrasting
confidence: 93%
“…CBT was proven to be superior to the traditional screw as regards less intra-operative blood loss (23,27,29) , shorter operative duration (24,29), shorter length of stay (23,27,29) , higher bone density (20,12,30) , higher improvement in JOA score (16) , lower incidence of ASD (16,29) and overall lower incidence of complications (19,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Sakaura et al (16) Compared with traditional screw: significantly higher improvement in JOA score, significantly lower ASD, non-statistically significant lower successful fusion rate Keorochana et al (19) Compared with traditional screw: significantly lower incidence of complications, nonstatistically significant different outcomes for pain VAS score (back and leg), disabilities score, JOA, intra-operative complications and fusion rates. Phan et al (20) Compared with traditional screw: greater bone density, but no difference in slippage at one year Asamoto et al (21) Significant improvement in JOA and VAS scores (100%), Bone fusion (89.1%) Gonchar et al (22) Fusion rate (99%), Compared with traditional screw: non-statistically significant higher improvement in JOA and VAS scores Marengo et al (23) Compared with traditional screw: Significantly shorter length of stay and less blood loss, significantly lower post-operative VAS and ODI scores, non-statistically significant higher fusion rate Sakaura et al (24) Compared with traditional screw: Significantly shorter operative duration and nonstatistically significant less intra-operative blood loss, higher recovery rate, less solid bony union, lower incidence of symptomatic ASD Wochna et al (25) Compared with pedicle screw: Significantly more intra-operative blood loss and nonstatistically significant shorter operative time and length of stay Hoffman et al (27) Compared with traditional screw: Significantly less intra-operative blood loss, shorter length of stay and non-statistically significant shorter operative time Karki et al (28) Compared with traditional screw, CBT has similar clinical outcome based on pain intensity, ODI status and JOA score as well as similar fusion rate and radiological evaluated complications Zhang et al (29) Compared with traditional screw: Significantly shorter operative duration and length of stay, less intra-operative blood loss, less incidence of complications, less incidence of ASD and ODI index Zhang et al (30) Compared with traditional screw: Significantly higher bone mineral density (9) Intra-operative cortical bone fracture at screw compression (8.3%) Rodriguez et al (10) No complications Glennie et al (11) Loss of reduction (50%), Screw loosening (37.5%) Ninomiya et al (15) Spacer backout (9.1%) Sakaura et al (16) Symptomatic ASD with need for additional reoperation (3.2%), Dural laceration (2.1%), Misplacement of pedicle screw (2.1%), Superficial wound infection (2.1%), Symptomatic hematoma (1.1%) Snyder et al (17) Thrombosis (3.8%), Hardware failure (2.5%), Pseudoarthrosis (2.5%), Deep wound infection requiring surgical debridement (1.3%), epidural hematoma (1.3%), Gonchar et al (22) Screw breakage (1.3%), Screw loo...…”
Section: Authorsmentioning
confidence: 99%